2020
DOI: 10.3390/ijms21165648
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs and Uveal Melanoma: Understanding the Diverse Role of These Small Molecular Regulators

Abstract: Uveal melanoma (UM) is a rare tumour of the eye, characterised by a high propensity to metastasise in half of all patients, most frequently to the liver. Although there are effective treatment options for the primary tumour, once metastasis has occurred prognosis is poor, with overall survival limited to months. Currently, there are no effective treatments for metastatic UM, despite the tumour having a well-defined signalling pathway to which many therapies have been directed. In an effort to develop novel tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 119 publications
1
11
0
2
Order By: Relevance
“…Robertson et al previously identified different miRNA clusters in UM which were associated with chromosome 3 status and also suggested that expression of some miRNAs might be related to the immune environment [11]. Similar to previous studies [11,[31][32][33][34][35], we observed a difference in miRs between low and high-risk UM.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Robertson et al previously identified different miRNA clusters in UM which were associated with chromosome 3 status and also suggested that expression of some miRNAs might be related to the immune environment [11]. Similar to previous studies [11,[31][32][33][34][35], we observed a difference in miRs between low and high-risk UM.…”
Section: Discussionsupporting
confidence: 89%
“…One of the problems when looking at miRs is that different studies identify different miRs as being relevant: as stated in an extensive review by Aughton et al [33], it should be noted that many studies looked at miRNAs in UM and hardly ever were the same miRNAs reported as significantly associated with an increased metastatic risk in UM. As they stated, differences may be due to differences in tissue sampling, classifications or miRNA detection systems.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Uveal melanoma (UM) metastasis results from the malignant progression of the disease, as well as the beginning of an adverse prognosis [1], which has a close association with the change of its molecular biological characteristics [2,3,4,5]. In relation to target molecule therapies, the selection of key target molecules has attracted the attention of many researchers.…”
Section: Backgroundsmentioning
confidence: 99%